The Development of Active Learning Based Stage Play Learning Media of Indonesia Language Theme 7 for Fourth Grade Primary School - Milliati Aulia Sabilla; Suyatno Suyatno (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2021)
The success of learning Bahasa needs to be supported by learning media that can condition students to be actively involved in learning. This study aims to develop active learning-based stage play learning media for Indonesian language lesson of Four grade which can be used to support the learning process to assist teachers in delivering the lesson. The research design of this study is research and development included steps of potential and problem analysis, data collection, product design, design validation, design revision, product trial, product revision, trial use and product revision, these steps of R&D were carried out in fourgrade state primary school 1 of Muntok, Bangka Regency. The data was collected through the observation then conducting the assessment by the expert and the questionnaire of student and teacher assessment. A qualitative and quantitative data were used to analyze the collected data. The research result showed that active learning-based stage play learning media for Bahasa lesson of theme 7 of fourth-grade primary school is feasibly used as learning media. Based on the expert assessment, the overall result of media, material, and learning expert is 75,3 with a feasible category. Assessment of learning practitioners was assisted by teachers of class 4 with 89 of very feasible category, and student assessment obtained 95 with very feasible category.